2006
DOI: 10.1029/2005gb002570
|View full text |Cite
|
Sign up to set email alerts
|

Mangroves, a major source of dissolved organic carbon to the oceans

Abstract: Organic matter, which is dissolved in low concentrations in the vast waters of the oceans, contains a total amount of carbon similar to atmospheric carbon dioxide. To understand global biogeochemical cycles, it is crucial to quantify the sources of marine dissolved organic carbon (DOC). We investigated the impact of mangroves, the dominant intertidal vegetation of the tropics, on marine DOC inventories. Stable carbon isotopes and proton nuclear magnetic resonance spectroscopy showed that mangroves are the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
281
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 423 publications
(299 citation statements)
references
References 32 publications
10
281
0
8
Order By: Relevance
“…Los bosques de mangle son importantes porque tienen las facultades de mejorar aspectos ecológicos como la dinámica de carbono orgánico (FloresVerdugo et al 1987, Bashan y Holguin 2002, Kristensen et al 2008 y productividad primaria (Holguin et al 2001, Dittmar et al 2006, además actúan como zona de protección contra huracanes y tormentas tropicales (Raven et al 1992, Gilman et al 2008, Komiyama et al 2008. A pesar de su importancia ecológica, los bosques de mangle están bajo constante degradación a nivel mundial debido a disturbios antropogénicos como el desarrollo de puertos en la zona costera, la ampliación de la frontera agropecuaria y la expansión de la acuacultura (Duke et al 2007, Polidoro et al 2010, Spalding et al 2010.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Los bosques de mangle son importantes porque tienen las facultades de mejorar aspectos ecológicos como la dinámica de carbono orgánico (FloresVerdugo et al 1987, Bashan y Holguin 2002, Kristensen et al 2008 y productividad primaria (Holguin et al 2001, Dittmar et al 2006, además actúan como zona de protección contra huracanes y tormentas tropicales (Raven et al 1992, Gilman et al 2008, Komiyama et al 2008. A pesar de su importancia ecológica, los bosques de mangle están bajo constante degradación a nivel mundial debido a disturbios antropogénicos como el desarrollo de puertos en la zona costera, la ampliación de la frontera agropecuaria y la expansión de la acuacultura (Duke et al 2007, Polidoro et al 2010, Spalding et al 2010.…”
Section: Introductionunclassified
“…Mangrove forests are important because they have the ability to improve ecological aspects such as organic carbon dynamics (Flores-Verdugo et al 1987, Bashan and Holguin 2002, Kristensen et al 2008) and primary productivity (Holguin et al 2001, Dittmar et al 2006, and they provide protection against hurricanes and tropical storms (Raven et al 1992, Gilman et al 2008, Komiyama et al 2008. Despite their ecological importance, mangrove forests around the world are constantly exposed to anthropogenic disturbances such as port development in the coastal zone, expansion of the agricultural frontier, and aquaculture expansion (Duke et al 2007, Polidoro et al 2010, Spalding et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that the composition of the NOM, rather than just the quantity, may play a key role in altering nickel toxicity to marine organisms. Mangroves are dominant habitats in the tropics and past studies have shown that mangrove-derived organic matter far exceeds that of terrigenic DOC in tropical coastal waters (Dittmar et al 2001;Dittmar et al 2006). It is recommended that further research investigate the influence of different sources of tropical marine DOC on relevant organisms to gain a better understanding of how this parameter determines the solubility and subsequent toxicity of nickel in tropical systems.…”
Section: Influence Of Water Quality Parameters On Nickel Toxicitymentioning
confidence: 99%
“…Mangroves are among the most productive ecosystems in the world (Kathiresan and Bingham, 2001;Alongi, 2009) and approximately 50% of the primary productivity of this ecosystem is exported to the oceans in the form of organic matter Dittmar and Lara, 2001;Jennerjahn and Ittekkot, 2002). The exportation of organic matter and dissolved nutrients from mangroves is important for the productivity of coastal waters because it has a known effect in food chains (Lugo and Snedaker, 1974;Alongi, 1990;Jennerjahn and Ittekkot, 2002;Dittmar et al, 2006).…”
mentioning
confidence: 99%